2003
DOI: 10.1002/nme.942
|View full text |Cite
|
Sign up to set email alerts
|

Extending the functionality of the general‐purpose finite element package SEPRAN by automatic differentiation

Abstract: SUMMARYFrom an abstract point of view, a numerical simulation implements a mathematical function that produces some output from some given input. Derivatives (or sensitivities) of the function's output with respect to its input can be obtained-free from truncation error-by using a technique called automatic di erentiation. Given a computer code in a high-level programming language like Fortran, C, or C++, automatic di erentiation generates another code capable of computing not only the original function but al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 10 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…This is a non-trivial task, and the SEPRAN package is one of the biggest codes successfully differentiated to date. In previous studies (Bischof et al 2003e) we reported on the differentiation of the SEPRAN package using the ADIFOR tool, and we also demonstrated the correctness of the sensitivities for the problem of a levitated droplet (Bischof et al 2003d). …”
Section: Derivatives Obtained With Automatic Differentiationmentioning
confidence: 74%
“…This is a non-trivial task, and the SEPRAN package is one of the biggest codes successfully differentiated to date. In previous studies (Bischof et al 2003e) we reported on the differentiation of the SEPRAN package using the ADIFOR tool, and we also demonstrated the correctness of the sensitivities for the problem of a levitated droplet (Bischof et al 2003d). …”
Section: Derivatives Obtained With Automatic Differentiationmentioning
confidence: 74%
“…AD (see e.g. Griewank [10], Bartholomew-Biggs et al [2], Bischof et al [4]) is a method to evaluate the derivative of a function specified by a computer program and represents an alternative solution to the numerical differentiation as well as to the symbolic differentiation. The AD technique is based on the fact that every computer program executes a sequence of elementary operations with known derivatives, thus allowing the evaluation of exact derivatives via the chain rule for an arbitrary complex formulation.…”
Section: Hybrid Symbolic-numeric Approachmentioning
confidence: 99%
“…The nodal unknowns form the vector of element unknowns p e = {u 1 , v 1 , u 2 , v 2 , u 3 , v 3 , u 4 , v 4 }. The hyperelastic strain energy density function W is formulated as a function of invariants of the right Cauchy strain tensor C = F T F and Lame constants λ and µ as follows…”
Section: Automation Of Primal and Sensitivity Analysis Of Hyperelastimentioning
confidence: 99%